2023
DOI: 10.1002/sd.2682
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive governance by community based organisations: Community resilience initiatives during Covid‐19 in Mathare, Nairobi

Jan Fransen,
Beatrice Hati,
Harrison Kioko Simon
et al.

Abstract: Adaptive governance describes the purposeful collective actions to resist, adapt, or transform when faced with shocks. As governments are reluctant to intervene in informal settlements, community based organisations (CBOs) self‐organize and take the lead. This study explores under what conditions CBOs in Mathare informal settlement, Nairobi initiate and sustain resilience activities during Covid‐19. Study findings show that CBOs engage in multiple resilience activities, varying from maladaptive and unsustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Likewise, the scarcity of local studies on DR limits the validation of findings on lower-level scales. To address this, we strongly advocate for in-depth case studies on specific hazard-induced disasters that provide deeper insights into DR at local scales in Africa.Such studies could supplement our findings by offering contextspecific knowledge on social dimensions of risks and resilience, like the insights provided by Vanclay (2016, 2021),Samaraweera (2024), Fransen et al (2024 and other local research captured in this work.…”
mentioning
confidence: 64%
“…Likewise, the scarcity of local studies on DR limits the validation of findings on lower-level scales. To address this, we strongly advocate for in-depth case studies on specific hazard-induced disasters that provide deeper insights into DR at local scales in Africa.Such studies could supplement our findings by offering contextspecific knowledge on social dimensions of risks and resilience, like the insights provided by Vanclay (2016, 2021),Samaraweera (2024), Fransen et al (2024 and other local research captured in this work.…”
mentioning
confidence: 64%
“…However, in order to overcome the mentioned negative effects of the crisis, they had to introduce various organizational and process changes, which we understand as adaptation measures in our study. There were already some efforts to describe how NGOs adapted to impacts of uncertainty and fast-changing conditions caused by lockdowns during COVID-19 pandemic [18,23,24]. However, we tried to conceptualize elements of such adaptation strategies that NGOs combined within their institution-specific conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the conditions of China, these strategies were focused on maintaining the cooperation with governments and local communities, as well as own self-improvement action [18]. Empirical studies carried out in developing countries also indicate the adoption of strategies focused on the strengthening of ties in local communities and the growth of the volume of collaborative projects between NGOs and other partners during the pandemic [23]. Results of Ahmed et al [24] suggest that NGOs have kind of natural ability to maintain resilience in times of emergencies, expressed in 4C framework including four components: (1) capability of problem assessment, (2) collaboration with stakeholders to pool resources, (3) compassionate leadership and (4) communication for quick and effective decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Fransen et al's (2024) case study on community‐based organizations (CBOs) during the COVID‐19 crisis in Mathare (Nairobi, Kenya) reveals the conditions that enable CBOs to initiate and sustain local community resilience. They found that bonding within the community, coordination with other actors, resources, organizational capacity, and network capacity were enabling conditions, while the lack of support from government, NGOs, and donor agencies was an impeding condition.…”
Section: The Local Community Dimension Of Resilience In Societymentioning
confidence: 99%